Utrapienie a prawdziwe ziemskie szczęście w nauczaniu Grzegorza Wielkiego - Kashchuk, Oleksandr (Vox Patrum, 2007)
The article discusses a question of the interrelation between suffering and real happiness of life on earth according to the teaching of Gregory the Great. The Pope teaches that the experience of suffering is related to the participation in real happiness, which consists in the possession of spiritual goods and joy as a result of such possession. Suffering purifies a person from sins and prevents a person from committing it. In suffering, every just person acquires virtues, solidifies and reveals them, and thus acquires the real happiness in life on earth. Therefore, Gregory the Great contends that just people, who are afflicted with suffering, are really happy people.